On the Production of Certainty in Public Health: Biopolitics and Speculative Objects - Castillo-Sepulveda, J; Bywaters-Collado, F; Galvez-Ramirez, M (UNIV SAO PAULO, FAC SAUDE PUBLICA, 2022)
This article analyzes the production of certainty in a health policy shaped by the epistemic scheme of evidence-based medicine: the Regime of Explicit Health Guarantees in Chile. Based on studies on science and technology, the analysis of material produced through focused ethnographies in ministry settings, and interviews with experts and professionals, this study exposes how objects linked to the evidence serve for three purposes in these scenarios: to reduce the complexity of global processes, to connect the local with the global, and to generate a new continuum that links truth with uncertainty. These objects are characterized here as "speculative objects," highlighting their important role in the articulation of rhetoric that allows the local configuration of biopolitics.